Images of a Complex World : the Art and Poetry of Chaos (With Cd-Rom). - Chapman, Robin (World Scientific Publishing Company, 2005)
With the poems written by winner of the Posner Poetry Award from the Council of Wisconsin Writers in 2005, this coffee-table book will delight and inform general readers curious about ideas of chaos, fractals, and nonlinear complex systems. Developed out of ten years of interdisciplinary seminars in chaos and complex systems at the University of Wisconsin-Madison, it features multiple ways of knowing: Robin Chapman's poems of everyday experience of change in a complex world, associated metaphorically with Julien Clinton Sprott's full-color computer art generated from billions of versions of on.